Salivary Atopy Biomarkers in Patients with Geographic Tongue - Farhad-Mollashahi, Leila; Dalirsani, Zohreh; Honarmand, Marieh; Salimi, Saeedeh; Shahabi Nezhad, Soudeh (European Journal of General Dentistry, 2021)
Objectives Geographic tongue is the mucositis of the dorsal surface of the tongue with no definite etiology, although it may be associated with atopic conditions. In this study, the salivary immunoglobulin E (IgE) and eosinophilic cationic protein (ECP) levels were assessed in patients with geographic tongue to examine the relationship between this condition and allergy-related biomarkers.Materials and Methods In this case-control study, unstimulated saliva was collected from 45 geographic tongue patients and 45 controls, and the salivary IgE and ECP levels were assessed. The data were analyzed with SPSS 20.0 using the Mann–Whitney test with a significance level of p < 0.05.Results The salivary IgE level in the case and control groups was 123.76 ± 8.1 and 74.34 ± 6.2 IU/mL, respectively, and the salivary ECP level was 9.4 ± 6.0 and 7.6 ± 3.2 ng/mL, respectively. There was a statistically significant difference between the two groups in terms of salivary IgE (p = 0.007) and ECP (p = 0.001) levels.Conclusion Salivary IgE and ECP levels increase in patients with geographic tongue. They can, therefore, be used for the initial diagnostic workup and to investigate the possible association of geographic tongue with allergic reactions.
Keywords: Geographic tongue; immunoglobulin E; eosinophil cationic protein; saliva; atopy